Tariff Wars as a Prisoner’s Dilemma: A CGE-Game Theory Analysis of Trump 2.0 vs. BRICS - Alana Sabila (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2026)
Backgrounds: The prospect of a “Trump 2.0” trade regime has revived concerns over universal tariffs and retaliation, especially for GVC-integrated emerging economies like Indonesia, where the key dilemma is whether unilateral or reciprocal tariffs provide strategic gains. Existing studies typically treat tariffs as exogenous CGE shocks or analyze tariff games separately, leaving the interaction between strategic behavior, general equilibrium effects, and value-chain transmission underexplored. Objectives: This study investigates whether strategically chosen bilateral tariffs between the United States and Indonesia within a broader US–BRICS context produce a non-cooperative Nash equilibrium and assesses its welfare, trade-balance, and GVC implications relative to cooperative outcomes. Methodology: An integrated framework is developed that nests a formal tariff game within a GTAP v11 CGE model. Bilateral tariff combinations of 0, 10, 20, and 30 percent are simulated to solve for Nash equilibrium and identify prisoner’s dilemma properties. Welfare, measured by equivalent variation, trade-balance changes, and TiVA-style backward and forward GVC indicators, are extracted under both welfare-based and mercantilist payoff structures. Findings: A unique Nash equilibrium emerges at zero tariffs. Any positive tariff reduces the initiator’s payoff, confirming a prisoner’s dilemma. Unilateral tariffs may temporarily improve Indonesia’s trade balance via import compression but generate larger welfare losses, while mutual protectionism harms welfare and trade balances through GVC disruptions. Conclusions: Tariff escalation is a dominated strategy once general equilibrium and value-chain effects are internalized. Coordination and targeted unilateral reforms dominate mercantilist protectionism, reinforcing free trade as the best response even under trade-balance-oriented preferences.